2011
DOI: 10.1007/s11442-011-0896-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal trends of climate change in Xinjiang, China

Abstract: Temperature and precipitation time series datasets from 1961 to 2005 at 65 meteorological stations were used to reveal the spatial and temporal trends of climate change in Xinjiang, China. Annual and seasonal mean air temperature and total precipitation were analyzed using Mann-Kendall (MK) test, inverse distance weighted (IDW) interpolation, and R/S methods. The results indicate that: (1) both temperature and precipitation increased in the past 45 years, but the increase in temperature is more obvious than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 35 publications
(24 reference statements)
5
76
1
Order By: Relevance
“…The value of H could be obtained by using the rescaled range statistic (R/S) analysis, which is a fractal theory for time series research and has been widely applied in geography, geology, climate change, economics, and other fields [37,[41][42][43]. The first step for calculating the Hurst exponents is to calculate the GDP elasticity of each indicator year-by-year (Supplementary Materials Tables S1-S5).…”
Section: Hurst Exponentmentioning
confidence: 99%
“…The value of H could be obtained by using the rescaled range statistic (R/S) analysis, which is a fractal theory for time series research and has been widely applied in geography, geology, climate change, economics, and other fields [37,[41][42][43]. The first step for calculating the Hurst exponents is to calculate the GDP elasticity of each indicator year-by-year (Supplementary Materials Tables S1-S5).…”
Section: Hurst Exponentmentioning
confidence: 99%
“…In some pixels of northwest of NW, the correlation values between light precipitation and grass NDVI are higher than those between heavy or moderate precipitation and grass NDVI, which indicated that light precipitation has stronger impact than moderate or heavy precipitation. The reason is that annual total precipitation in the region was mostly less than 150 mm and heavy precipitation is rare [61], but same threshold values (compared to the entire RAA) for defining precipitation intensity levels were used. Table 2.…”
Section: Response Of Grass Ndvi To Precipitation Intensitymentioning
confidence: 99%
“…This study provided insights into the dynamic relationship between the dominant modes of climate variation in the northern hemisphere and seasonal precipitation. Li et al 2 evaluated the variation in seasonal and annual precipitation using the Hurst exponent and Mann-Kendall (MK) test methods in Xinjiang, China. Xue et al 3 decomposed the autumn precipitation series in the Weihe River Basin, China, using the ensemble empirical mode decomposition (EEMD) method and determined the precipitation periodicity characteristics at various scales.…”
mentioning
confidence: 99%
“…The Huangfuchuan River has a length of 137 km and the watershed area is 3246 km 2 . The annual precipitation is 350-450 mm, and >80% of the precipitation falls during the period JuneSeptember.…”
mentioning
confidence: 99%
See 1 more Smart Citation